(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
The work presented here " Compared logic in social organizations. A Proposed Curriculum", is a gnoseológic research. It made use of qualified documents handling necessary categories related to knowledge philosophy. It has confronted reason models to face complexity involving both social and professional relationships from Lisandro Alvarado University / DAC Administration and Accounting Faculty graduates. It is imperative to mention that a model of reason manages to interpret and explain reality going through the path guiding their processes both real and abstract; such models are called logic. Logic guides thinking to interpret reality. This work main interest focuses on the typical processes of social organizations whose complexity seeks to ensure a thinking approach beyond linear thinking based on logical analysis. That is why it’s necessary to complement careers curriculum from this Faculty regarding topics that have to do with these logics currently absent in the academic path. Hence the motivation for this work, which aims to propose an instructional program oriented towards the study of logics and support laws, they are: analytical logic and dialectic logic.